The effect of Turbo Trainer cycling on pedalling technique and cycling efficiency - Arkesteijn, M.; Hopker, J.; Jobson, S. A.; Passfield, L. (International Journal of Sports Medicine, 2013)
Cycling can be performed on the road or indoors on stationary ergometers. The purpose of this study was to investigate differences in cycling efficiency, muscle activity and pedal forces during cycling on a stationary turbo trainer compared with a treadmill. 19 male cyclists cycled on a stationary turbo trainer and on a treadmill at 150, 200 and 250 W. Cycling efficiency was determined using the Douglas bags, muscle activity patterns were determined using surface electromyography and pedal forces were recorded with instrumented pedals. Treadmill cycling induced a larger muscular contribution from Gastrocnemius Lateralis, Biceps Femoris and Gluteus Maximus of respectively 14%, 19% and 10% compared with turbo trainer cycling (p<0.05). Conversely, Turbo trainer cycling induced larger muscular contribution from Vastus Lateralis, Rectus Femoris and Tibialis Anterior of respectively 7%, 17% and 14% compared with treadmill cycling (p<0.05). The alterations in muscle activity resulted in a better distribution of power during the pedal revolution, as determined by an increased Dead Centre size (p<0.05). Despite the alterations in muscle activity and pedalling technique, no difference in efficiency between treadmill (18.8±0.7%) and turbo trainer (18.5±0.6%) cycling was observed. These results suggest that cycling technique and type of ergometer can be altered without affecting cycling efficiency.